Computerized analysis of seedlings in the evalution of vigor of Brachiaria brizantha cv. Marandu seeds - Jeromini, Tatiane Sanches [UNESP]; Barros, Renato Teo de [UNESP]; Silva, Givanildo Zildo da; Martins, Cibele Chalita [UNESP] (Univ Federal Rural Pernambuco, 2018)
Computerized image analysis is a simple and rapid method of evaluating seed vigor, with proven efficiency for several species. The aim of this work was to evaluate the vigor of Brachiaria brizantha cv. Marandu by means of the computerized analysis of seedlings in comparison with the traditional tests. Seeds of five seed lots of B. brizantha cv. Marandu were evaluated for water content, germination, first counting, accelerated aging, emergence of field seedlings, emergence speed index and computerized analysis of seedlings images (SVIS (R)), with average values of growth rates, uniformity of development and vigor, in a completely randomized experimental design. Computerized seedling analysis compared to traditional tests was not efficient in evaluating seed vigor of B. brizantha cv. Marandu.
Keywords: forage grass; physiology quality; SVIS (R)